If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4a + -3b + 5c) = 0 (4a * -1 + -3b * -1 + 5c * -1) = 0 (-4a + 3b + -5c) = 0 Solving -4a + 3b + -5c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. -4a + 3b + -3b + -5c = 0 + -3b Combine like terms: 3b + -3b = 0 -4a + 0 + -5c = 0 + -3b -4a + -5c = 0 + -3b Remove the zero: -4a + -5c = -3b Add '5c' to each side of the equation. -4a + -5c + 5c = -3b + 5c Combine like terms: -5c + 5c = 0 -4a + 0 = -3b + 5c -4a = -3b + 5c Divide each side by '-4'. a = 0.75b + -1.25c Simplifying a = 0.75b + -1.25c
| x=b-8/a-1 | | factorx^2+10x-24=0 | | 7k+3=5 | | Y=9-2x+3 | | 5=-16x^2+45x+6 | | Y=5x^2-7x-6 | | 7w-5=-4(w-7) | | 12a-9=3 | | ln(x)-ln(5)=5 | | -32=-8u | | log(4x+24)=3 | | 5=16/x | | (3x+14)=(7x) | | 63=25x | | -28x^2-32x+16=0 | | -x^2+4.5x+1=0 | | 5/1=16/x | | x^2=420 | | 2(k+7)=32 | | 2x+5x-10+3=6x-7.2+x | | 4A=(B+b)*h | | 4x^3+8x^2+5x=0 | | -8x-2x=-56+48 | | 60=3.5x-0.05x^2 | | 5x-3(2x-9)=28 | | 1x=7x+42 | | 39=4x+5 | | 3x+x(2+2)+10=5(x^2+2)-3(x^2-1) | | 1x+0.4x=1 | | 2n4=6/9 | | √36x^2/4x^6 | | X+27-14=-15 |